Remodelling of supraspinal neuroglial network in neuropathic pain is featured by a reactive gliosis of the nociceptive amygdala. (27th November 2012) - Marcello, L.; Cavaliere, C.; Colangelo, A.M.; Bianco, M.R.; Cirillo, G.; Alberghina, L.; Papa, M.
Abstract Background Many brain areas participate to supraspinal control of nociception. In these regions, few studies have investigated the role of glial cells in supraspinal plasticity and the effect of 7‐day intrathecal nerve growth factor‐like (BB14®, Blueprint Biotech, Milano, Italy) treatment. Methods In male Sprague‐Dawley rats, we evaluated by immunohistochemistry the morphological and molecular rearrangement of neuroglial network occurring in several supraspinal brain regions involved in pain processing following spared nerve injury (SNI) of the sciatic nerve. In particular, the medial prefrontal cortex, the amygdala (Amy), the nucleus accumbens (Acb), the thalamus and the periaqueductal gray were analysed. Results Despite the modifications occurring in the dorsal horn of spinal cord following SNI, no significant changes in the Iba1 and glial fibrillary acidic protein (GFAP) expression were detected in all the analysed supraspinal regions, except for the Amy, showing a remarkable GFAP increase. Interestingly, neuropathic rats also displayed a significant increase of glial transporters (GTs) in all the supraspinal regions. Finally, the analysis of vesicular glutamate transporter 1 (vGLUT1) and vesicular gamma‐aminobutyric acid (GABA) transporter (vGAT) expression revealed a significant enhancement of glutamatergic/GABAergic ratio in all selected brain regions of SNI animals, except for Acb. Both glial activation in the Amy and alteration of GTs and vGLUT/vGAT levels observed in neuropathic animals were largely reversed by BB14® treatment. Conclusions All together, these data strengthen the role of supraspinal neuroglial network plasticity in the establishment of neuropathic pain syndrome. The hallmark is represented by the divergence between glial reaction confined to Amy and the widespread changes in the GT distribution and glutamate/GABA ratio detected in the other supraspinal region.